THE FEATURES OF APPLICATION OF MICROGEOPHYSICAL RESEARCHES FOR STUDYING OF FLOODING OF SOILS (BY AN EXAMPLE CHERNOBAIVSKA'S AREA) - ONYSHCHUK, I.; REVA, M.; NIKITASH, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Moveover, we get the peculiarities of technique geophysical researches on a study of waterflooding of the soils is showing. The geoelectrical parameters of the various soil types and roks of upper part section and the principles of geoelectric mapping of landwaterflood.